(untitled) (American Journal of Youth and Women Empowerment, 2024)
The current article explores the contribution of Morocco’s National Initiative for Human Development (NIHD) to women’s economic empowerment and integration in society through the art of cooking. With targeting Lalla Moulati, it is a pastry-specialized institution which works under the supervision of the NIHD. This means that they share a common objective. Simply put, Lalla Moulati aims at encouraging women to take part in the job market and become financially independent rather than remaining a dependent burden who needs to be taken care of. In this regard, this article targets unveiling the multifaceted impact of such initiatives on women’s personal, societal and economic status. Using the qualitative approach solely, this study provides a detailed examination on how this institution’s plans and accomplishments align with the objectives of the NIHD. Using interviews, this article aims at examining the extent to which Lalla Moulati plays a pivotal role in not only changing women’s lives, but also challenging the traditional mindset that bounds women to specific gender roles. By examining the experiences of women in the domain of pastries through this institution, this research highlights the major role of vocational training in the advancement of women’s socio-economic position in Moroccan society.